New Data on Seed Coat Micromorphology of Several Impatiens spp. from Northeast India - Agnieszka Rewicz; Wojciech Adamowski; Souravjyoti Borah; Rajib Gogoi (Acta Societatis Botanicorum Poloniae, 2020)
This study aimed to analyze the seed coat structure of nine species from the genus Impatiens from Northeast India. A review of the available literature showed a scarcity of data on seed sizes and shapes, as well as a complete lack of information on the ultrastructure of seeds from five taxa of Impatiens determined with a scanning electron microscope (SEM). Photographs of the surface structure of seeds from the analyzed species were taken using an SEM and, from these, we measured the length and width of the seeds. The results showed differences in the seed ultrastructure and metric traits within the studied taxa. Based on the ornamentation of the epidermal cells, we distinguished three morphological types: protrusive, granulate, and reticulate. The seeds of the investigated species had ellipsoid, subellipsoid, or subspheroid shapes. Their lengths and widths ranged from 1.2 to 3.6 mm and 0.7 to 2.1 mm, respectively. The results of the study showed that the ultrastructures of Impatiens seeds are different among taxa and for some species can be used as a diagnostic character for their identification.